ANALISIS POTENSI, EFEKTIFITAS DAN KONTRIBUSI PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN TANA TORAJA - Tonapa, Hesty Reny; Saerang, David; Mawikere, Lidia (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
The purpose of this study was to calculate how much is the potential, the effectiveness and contributions of Hotel taxes in Tana Toraja as one of the source of regional revenue. This research is using descriptive method by analyzing the realization data of hotel Taxes in 2011-2015. The results showed that the potential of hotel taxes has not been achieved optimally because the actual revenues still well below its potential and the difference between the actual and potential of hotel taxes reached Rp. 891,981,757 in 2015. The results of this study also shows that the effectiveness of hotel taxes has been effective where the level of effectiveness of hotel Taxes has reached the effectiveness criteria.Keywords: PAD, Potency, Effectiveness